Evaluating the usefulness of C5 and C5AR1 as genetic biomarkers of IgA-mediated vasculitis - Joao Carlos Batista-Liz; Vanesa Calvo-Río; María Sebastián Mora-Gil; María Teresa Leonardo; Ana Cristina Peñalba; Luis Martín-Penagos; Javier Narváez; Belén Sevilla-Pérez; José Luis Callejas-Rubio; Ligia Gabrie; Rafael Gálvez Sánchez; Luis Caminal-Montero; et al. (Molecular Medicine)
Abstract Background IgA-mediated vasculitis (IgAV) is a complex inflammatory disease. Unravelling its genetic background would allow us to identify genetic biomarkers that may be used as additional tools in its daily management, helping to solve the clinical challenge that this vasculitis entails. C5 is a potent immune mediator that is proteolytically processed to generate C5a, a potent anaphylatoxin that exerts its function via C5aR1. C5 downstream variants (rs3761847 and rs10818488) have been recently related to IgAV pathogenesis. Additionally, C5a and C5aR1 dysregulation contributes to the development of inflammatory diseases, and, particularly, elevated C5a plasma levels have been observed in IgAV patients in the acute stage. Accordingly, we aimed to evaluate the influence of C5 and C5AR1 on the pathophysiology of IgAV. Methods Eight C5 (rs10760128, rs74971050, rs4310279, rs7868761, rs10818495, rs10156396, rs3815467, and rs16910280) and three C5AR1 (rs10853784, rs11673071, and rs11670789) tag variants were genotyped in 342 Caucasian IgAV patients and 723 ethnically matched healthy controls. Results No statistically significant differences were observed when C5 and C5AR1 frequencies were compared between IgAV patients and healthy controls. Likewise, similar C5 and C5AR1 frequencies were observed amongst IgAV patients stratified according to IgAV severity (presence/absence of nephritis). Furthermore, no C5 and C5AR1 differences were disclosed when IgAV patients were stratified according to demographic and clinical IgAV characteristics other than nephritis (age at disease onset, presence/absence of joint and gastrointestinal manifestations) and sex. Conclusions Our results suggest that C5 and C5AR1 are not related to IgAV pathogenesis and, therefore, these genes may not be useful as IgAV genetic biomarkers.